Esthétique de l’imaginaire et enjeux spiritualistes : La Terre avant le déluge de Figuier et L’Univers de Pouchet - Percheron, Bénédicte (Studia Romanica Posnaniensia, 2018)
Science popularization books, La Terre avant le déluge by Louis Figuier and L’Univers: les infiniment grands et les infiniment petits by Félix-Archimède Pouchet, represent the success of science popularization publishing of this period and the desire to spread naturalistic knowledge far and wide. With a spiritual approach to nature, they underline the important epistemological stakes of this period. The aim of this study is to question the literary, stylistic and formal strategies to assert or underline thoughts on nature in these books.